Sensitivity analysis of a crawl gait multi-objective optimization system - Oliveira, Miguel (2013)
This paper describes the analysis of a crawl gait multi-objective optimization system that combines bio-inspired Central Patterns Generators (CPGs) and a multi-objective evolutionary algorithm. In order to optimize the crawl gait, a multiobjective problem, an optimization system based on NSGAII allows to find a set of non-dominated solutions that correspond to different motor solutions The experimental results highlight the effectiveness of this multi-objective approach.